Correlation Between Knowledge, Attitudes, and Behavior with Blood Cadmium Levels in the Population of Industrial Area - Teuku Heriansyah1, Kumboyono Kumboyono2 , Fibe Yulinda Cesa3 , Titin Andri Wihastuti4 , Shila Wisnas (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: The aim of this analysis is to investigate the correlation between knowledge, attitude, andbehavior with cadmium level in the industrial population. Methods: This research is a non-experimentalstudy with cross-sectional method. The subjects are 108 respondents live in industrial area. Questionnaireswere used for measuring the level of knowledge, attitude, and behavior. Cadmium levels were measured usingAtomic Absorption Spectrophotometry (AAS). Results: The result showed a strong correlation betweenlevels of knowledge factor and cadmium with r = -0,272* in the population of industrial areas. Meanwhile,knowledge have significant correlation with attitude (r = 0.528**). Conclusion: Knowledge factor hasthe significant relationship with cadmium levels in the population of industrial area. The government issuggested to improve the knowledge of the people in the industrial area in order to prevent high levels ofcadmium. Therefore, the negative impact of metal waste exposure on health can be minimized.